Shahrisabz va maydanak baland tog‘ turistik markazining ekoturistik imkoniyatlaridan samarali foydalanish masalalari - Yarashev, Q.S; Badalov, O.B; Yusupov, B.B (SCIENCE and SOCIETY, 2025)
The article is devoted to the ecotourism potential of the Shakhrisabz and Maidanak high-mountain tourist centers and their effective use. The main attention is paid to the development of promising tourism sectors in the mountain- ous and foothill regions of the basin.
Keywords: mountain ecotourism; natural waterfalls; forests; rivers; caves; lakes; holiday homes and sanatoriums